The effect of time-saving household appliance ownership on outcomes for children and married women: Evidence from India - Smriti Bhargava; Amanda Kerr (IZA Journal of Labor Policy, 2022)
We use microlevel data from the India Human Development Survey to test our hypothesis that ownership of time-saving household appliances results in the following: an increase in employment rates for married women; an increase in school enrollment rates; and a decrease in employment rates for children. We address the concern of endogeneity of appliance ownership by instrumenting household ownership of time-saving appliances by two family-specific time-using household assets and (1) average ownership rate among single women living in the same primary sampling unit (for the adult female sample) or (2) average ownership among households with no children living in the same primary sampling unit (for the child sample). Our results suggest a decrease in married women's and children's employment when ownership of time-saving appliances increases. Disaggregating our measure of employment, we find that married women use time-saving appliances as a substitute for human capital and increase their probability of working in more productive employment outside of the household.
Keywords: J16; J22; I25; 330; household appliances; home production; India